Maternal gluten, cereal, and dietary fiber intake during pregnancy and lactation and the risk of islet autoimmunity and type 1 diabetes in the child - Hakola Leena; Lund-Blix Nicolai A.; Takkinen Hanna-Mari; Tapanainen Heli; Niinistö Sari; Korhonen Tuuli E.; Stene Lars C.; Hyöty Heikki; Toppari Jorma; Ilonen Jorma; Knip Mikael; Veijola Riitta; et al. (Elsevier, 2025)
Background & aims Maternal gluten intake in relation to child's risk of type 1 diabetes has been studied in few prospective studies considering the diet during pregnancy but none during lactation. Our aim was to study whether gluten, cereals, or dietary fiber in maternal diet during pregnancy and lactation is associated with the risk of islet autoimmunity or type 1 diabetes in the offspring.
Methods We included 4943 children with genetic susceptibility to type 1 diabetes from the Finnish Type 1 Diabetes Prediction and Prevention (DIPP) Study, born between 1996 and 2004. Maternal intake of gluten, different types of cereals, and dietary fiber were derived from a semi-quantitative validated food frequency questionnaire covering the eighth month of pregnancy and the third month of lactation. Children were monitored for islet autoantibodies up to age of 15 years and type 1 diabetes until year 2017. Risk of islet autoimmunity and clinical type 1 diabetes were estimated using Cox regression model, adjusted for energy intake, child's sex, HLA genotype, and familial diabetes.
Results Altogether 312 children (6.4%) developed islet autoimmunity at median age of 3.5 (IQR 1.7, 6.6) years and 178 children (3.6%) developed type 1 diabetes at median age of 7.1 (IQR 4.3, 10.6) years. Gluten intake during pregnancy was not associated with islet autoimmunity (HR 0.96; 95% CI 0.68, 1.35), per 1 g/MJ increase in intake nor type 1 diabetes (HR 0.96; 95% CI 0.62, 1.50) in the offspring. Higher barley consumption during lactation was associated with increased risk of type 1 diabetes (HR 3.25; 95% CI 1.21, 8.70) per 1 g/MJ increase in intake. Maternal intake of other cereals or dietary fiber was not associated with the offspring outcomes.
Conclusions We observed no association between maternal intake of gluten, most consumed cereals, or dietary fiber during pregnancy or lactation and the risk of islet autoimmunity or type 1 diabetes in children from a high-risk population.